The associations between the final clinical practicum elements and the transition experience of early career nurses: A cross-sectional study - Kaihlanen AM; Elovainio M; Haavisto E; Salminen L; Sinervo T. (Netherlands, 2022)
The final clinical practicum before graduation prepares nursing students for the transition from a student to a nurse, but the essential elements of the final clinical practicum that enhance successful transition are not known. We examined the associations of five elements of the final clinical practicum with four indicators of the transition experience in new nurses. We also tested whether psychosocial work characteristics modified these associations. The study sample comprised 712 Finnish nurses who had graduated within the previous two years before the data collection (response rate: 18%). The data were collected using a questionnaire survey in 2018. The elements of the final clinical practicum included (1) the systematicness of the practicum, (2) teacher involvement, (3) the quality of supervision, (4) preparing for the demands of a nurse's work and (5) being part of a professional team. Our results, based on linear regression analysis, showed that all the elements except the quality of supervision were associated with indicators of the transition experience (beta range: from 0.08 to 0.35). Job demands modified several of these associations. The findings of this study highlight the potential for well-implemented final clinical practicums to promote a smoother transition for new nurses.